P587 Drug survival of vedolizumab-treated inflammatory bowel disease patients in a nationwide observational cohort study: ICC case series. (16th January 2018) - Biemans, V; van der Woude, C; Dijkstra, G; van der Meulen - de Jong, A; Oldenburg, B; de Boer, N; Ponsioen, C; de Vries, A; Haans, J; Pierik, M; Hoentjen, F; ,
Abstract: Background: Vedolizumab (VDZ) is an antibody blocking the α4β7 integrin. Obtaining clinical response can take up to 3–6 months but once obtained seems to be well maintained at least throughout Week 52. However, real-life drug survival data beyond Week 52 are scarce. We therefore aimed to assess the drug survival in our 2-year observational cohort of VDZ-treated inflammatory bowel disease (IBD) patients. Methods: IBD patients who started VDZ in standard care were included. Patients were followed for 2 years using a systematic follow-up. We registered clinical disease activity (Harvey Bradshaw Index (HBI) and Short Clinical Colitis Activity Index (SCCAI)), inflammatory biomarkers (CRP and faecal calprotectin), hospital admissions, surgery, adverse events, and VDZ discontinuation. Dependent t test and Wilcoxon-signed rank test was used. Results: We enrolled 266 patients (172 CD, 153 female, aged 40.7 ± 15.1 years, disease duration 12.4 ± 9.5 years). 98.8% (CD) and 80.3% (UC) were biological-experienced. At baseline 29.7% of CD patients used concomitant corticosteroids, 19.2% immunosuppressants (IMM) and 11.6% used both. For UC, 30.9% used corticosteroids, 19.1% IMM and 18.1% both. A total of 121 (45.4%) IBD patients discontinued VDZ after a median follow-up of 25.7 (IQR 16.6–44.9) weeks for CD and 20.4 (14.9–30.4) weeks for UC. Main reason was primary non-response (71.1%), while adverse accounted for only 5%. Drug survival of VDZ did not differ between CD and UC patients ( p = 0.49). VDZ discontinuation occurred for 66 (24.8%) IBD patients (55 no response, 3 adverse events) before 26 weeks of treatment. Beyond 52 weeks, 19 IBD patients (10 loss of response) discontinued VDZ. At Week 12 a difference in SCCAI was found between responders and non-responders (mean decrease of responders 3.4 ( ± 3) vs. 0.5 ( ± 3.7) non-responders p = 0.001). While the median treatment duration was 20.4 weeks for UC non-responders (IQR 16.9–28.6). Conclusions: In a real-life IBD cohort, discontinuation rates for VDZ were 24.8% at Week 26, 38.3% at Week 52, and only 7.1% beyond Week 52. The main reason for all discontinuation was primary non-response (71.1%) in contrast to adverse events (5%). A decrease in SCCAI at Week 12 was predictive of clinical response to VDZ. Our long-term VDZ data show a reassuring drug survival and safety profile beyond 52 weeks in daily clinical practice.